Isolation of some fungal agents for sub acute mastitis cows inAL-Anbar province - K. luaibi, Oday; M. Radhy, Amanee; H. Salman, Ammar (Iraqi Journal of Science, 2023)
This study was designed for isolation of some fungi that caused sub clinical mastitis in cow milk in AL-anbar governorate in Iraq . Total number of 100 milk samples were collected from 25 cow in AL- Falluja city , by using of California mastitis test 45% of milk samples were infected with sub clinical mastitis ,while 55% of milk samples were negative for California mastitis test. The results showed of fungal isolation of milk samples which were positive for California mastitis test, recording 19 isolates of different types of fungi : Aspergillus fumigatus2.2% , Aspergillus niger 4.4% , Candida albicans 26.6% , Blastomced dermetitidis% 4.4 and Geotrichum candidum4.4%. The isolation of these types of fungi, may be attributed to many factors like Poor management ,treatment with corticosteroid and antibiotic compound for long times, As well as the unfavorable climate conditions and neglecting the bursts during the first milking are all factors that create and increase the chance of fungal mastitis